The association between peptic ulcer diseases and mental health problems: A population-based study. Issue 34 (August 2017) - Lee, Young Bok; Yu, Jihan; Choi, Hyun Ho; Jeon, Bu Seok; Kim, Hyung-Keun; Kim, Sang-Woo; Kim, Sung Soo; Park, Yong Gyu; Chae, Hiun Suk
Abstract : Abstract: This study aimed to investigate the association between the prevalence of peptic ulcer disease (PUD) and mental health problems, such as severe stress, depressive mood, and suicidal ideation. The population-based cross-sectional study was comprised of 14, 266 subjects participating in the fourth annual Korea National Health and Nutrition Examination survey from 2007 to 2009. The participants were divided into 2 groups according to the self-reported questionnaires: the PUD group and the non-PUD group. The association between PUD and mental health problems, such as severe stress, depressed mood, suicidal ideation, and psychological counseling history, were evaluated by using multivariate analysis and logistic regression. Among the 14, 266 participants over 19-years old, 813 participants (5.6%) had PUD. Compared to the non-PUD group (n = 13, 453), the PUD group had a significantly higher percentage of males, current smokers, and heavy drinkers, lower education status, lower income, and greater presence of diabetes mellitus, hypertension, metabolic syndrome and mental health problems, including severe stress, depressed mood, suicidal ideation, and psychological counseling history. After adjustment for lifestyle and medical and environmental factors, mental health problems were found to be associated with a significantly higher risk for PUD. Psychological problems, such as severe stress, depressed mood, suicidal ideation, and psychological counseling, were associated with PUD prevalence.